2018
DOI: 10.1111/eip.12747
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' views towards diagnosing and treating depression in five southeastern European countries

Abstract: Aim: To assess and compare general practitioners' (GPs') views of diagnosing and treating depression in five southeastern European countries. Methods:A cross-sectional study was conducted in Albania, Bulgaria, Moldova, Romania, and Serbia. The sample included 467 GPs who completed a hard-copy self-administered questionnaire, consisting of self-assessment questions related to diagnosing and treating depression. Results:The most common barriers to managing depression in general practice reported by GPs were: pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Regarding therapeutic approach, the percentage of physicians that prescribe medication (56.1%) is significantly lower than that reporting awareness (77.8%) of the appropriate medication for the disease they have diagnosed. In a cross-sectional study from five southeastern European countries, even though 40.9% of GPs state that can treat depression with medication, 79.4% believe patients in need of antidepressants should do better if referred to a psychiatrist [ 22 ]. A questionable therapeutic approach of GPs is highlighted in an Italian study, as 35% from those who initiated treatment, were in fact false-positive cases of depression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding therapeutic approach, the percentage of physicians that prescribe medication (56.1%) is significantly lower than that reporting awareness (77.8%) of the appropriate medication for the disease they have diagnosed. In a cross-sectional study from five southeastern European countries, even though 40.9% of GPs state that can treat depression with medication, 79.4% believe patients in need of antidepressants should do better if referred to a psychiatrist [ 22 ]. A questionable therapeutic approach of GPs is highlighted in an Italian study, as 35% from those who initiated treatment, were in fact false-positive cases of depression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Close collaboration with mental health specialists, in both training and practice, is of eminent importance. In order to guide an efficient support of mental disorders at the primary healthcare, the following recommendations are deduced from this study, also supported by the literature: i) theoretical learning should be accompanied by practical training, so that education is tied with real clinical practice [ 4 ], ii) an efficient model of outpatient consult liaison psychiatry, like the collaborative care model [ 31 , 32 ] should be developed, that enhances the skills of GPs to manage psychiatric patients, and iii) adequate time for diagnosis, counselling, self-study and consultation should be given to GPs, along with incentives to be deeply involved in the management of mental disorders [ 4 , 7 , 15 , 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that women are more likely to be depressed in countries in which they have lower income, and lower socio-economic status. Women are more likely to be prescribed with more antidepressants than men are, which may be associated with higher prevalence reported [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the education and practice in Serbia, general practitioners should be able to recognize the depression and refer the patient to the psychiatry treatment. The study among general practitioners in five Southeastern Europe countries showed that the majority of our general practitioners consider recognizing the depression as their responsibility [22].…”
Section: Introductionmentioning
confidence: 97%
“…In 2017, the World Health Organization (WHO) reported that depression, which affects 322 million people globally, is the second leading cause of the World’s medical burden. It is expected that by 2030, depression will become the most common disabling condition ( Duric et al, 2018 ). Depression is a common disease with low mood, lack of interest, fatigue, and other core symptoms.…”
Section: Introductionmentioning
confidence: 99%